Environmental governance: alaw enforcement 12.305/10 in the cities of greater population of the state of Paraná - Bauer, Thiago; Shimohigashi, Ednar Rafaela Mieko; Jorgeto, Fernando Alberto; Oliveira, Ednilson Barbosa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article was motivated by the need of the intervention of the government on environmental issues, particularly in solid waste management, through the collection, disposal and recycling of the material, whether recyclable or organic. Law 12,305/10 provides for the National Solid Waste Policy, which shows the importance of the participation of the entire population, blaming from the waste generators to the government in case of breaches. The states and municipalities, it is the development of state and municipal levels of solid waste management. This article is qualitative, descriptive and it is used bibliographic references. This research has prioritized the search for information on the adequacy of municipalities to Law 12,305 / 10, and was delimited to 10 cities with most of Paraná state's population, a survey of the main items of municipal plans, through official information of Municipalities, Municipal Environment, Environment State Ministry of Environment, as well as collected from news organizations data.